2014
DOI: 10.18632/oncotarget.2194
|View full text |Cite
|
Sign up to set email alerts
|

The NF1 gene revisited - from bench to bedside

Abstract: Neurofibromatosis type 1 (NF1) is a relatively common tumour predisposition syndrome related to germline aberrations of NF1, a tumour suppressor gene. The gene product neurofibromin is a negative regulator of the Ras cellular proliferation pathway, and also exerts tumour suppression via other mechanisms.Recent next-generation sequencing projects have revealed somatic NF1 aberrations in various sporadic tumours. NF1 plays a critical role in a wide range of tumours. NF1 alterations appear to be associated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 180 publications
0
111
0
9
Order By: Relevance
“…NF1 encodes neurofibromin, which functions as a tumour suppressor via inactivation of RAS oncogene that serves to downregulate mitogen-activated protein kinase and the PI3K/AKT/mTOR pathway. Somatic NF1 alterations have been reported in various sporadic tumours including glioblastoma, melanoma, cancers of ovary, breast and lung, hematolymphoid malignancy and sarcoma 42. Data on NF1 in cholangiocarcinoma are limited; 1 of 28 IHCCA was found to harbour somatic NF1 mutation using an NGS-based platform 32…”
Section: Discussionmentioning
confidence: 99%
“…NF1 encodes neurofibromin, which functions as a tumour suppressor via inactivation of RAS oncogene that serves to downregulate mitogen-activated protein kinase and the PI3K/AKT/mTOR pathway. Somatic NF1 alterations have been reported in various sporadic tumours including glioblastoma, melanoma, cancers of ovary, breast and lung, hematolymphoid malignancy and sarcoma 42. Data on NF1 in cholangiocarcinoma are limited; 1 of 28 IHCCA was found to harbour somatic NF1 mutation using an NGS-based platform 32…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on the mutation profile of melanomas reported a frequency of NF1 mutations in 16 of 121 (13%) tumors 29 , and in 13 of 91 (14%) 30 , respectively. In a recent review the overall frequency of NF1 mutations was estimated at 14% of cutaneous melanomas, with a total of 475 specimens analyzed 31 . No information was provided about the histopathologic subtype, but it is unlikely that a significant number of DM was included in those studies, because DM is a rare variant of melanoma (approximately 4 % of primary melanomas) 3, 32 .…”
Section: Discussionmentioning
confidence: 99%
“…NF1 is 1 of 6 genes significantly mutated in both subtypes, implying a potential driver pathway that warrants further study in both subtypes. Nonetheless, the number clinical trials of NF1-based therapeutic approaches are currently limited (8). Improved understanding of the implications of NF1 aberrations is critical for the development of novel therapeutic strategies.…”
Section: Newly Identified Mutation Driversmentioning
confidence: 99%